The Strategy of Taiwan Digital Diplomacy Association (TDDA) for Taiwan’s International Presence - Eva Ermylina (Andalas Institute of International Studies, 2023)
This paper examines Taiwan Digital Diplomacy Association (TDDA) 's strategy for gaining public awareness of Taiwan’s international presence. As a non-governmental and non-profit organization, TDDA can be classified as a civil society that has a pure interest. Unlike other civil society organizations which focus on human rights, justice, or environmental issues, the goal of TDDA is to promote Taiwan on the global stage. By using digital platform and actively campaigning on social media such as Twitter, Facebook, and Instagram, TDDA acts as a part of citizen diplomat and helps the country reaches its goal which is to be present in the international community since Taiwan is isolated by China due the Cross-Strait issue and One China Policy. Moreover, this paper is a descriptive and qualitative research which is analysed by using the concept of civil society. The data is collected from interviewing the project manager of TDDA, research journals, and the internet sources such as official websites and social media. It can be mentioned that TDDA uses two main strategies to get its aim namely advocating and networking. However, how effective this strategy is not explained in this paper, the research about that topic might be done in the future.